Composite copper components treated with silane coupling agents
The composite copper foil with acicular copper oxide, nickel, and silane coupling agent layers addresses adhesion and transmission loss challenges, enhancing mechanical and chemical adhesion and reducing frequency loss through precise silane application.
Patent Information
- Application Number
- JP2021567457
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-12-21
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-12-21
AI Technical Summary
Existing copper foils for printed wiring boards face challenges in achieving both good adhesion to resin base materials and reducing transmission loss in high frequency bands, with the optimal amount of silane coupling agent varying based on surface roughness and type of metal laminated on the copper foil.
A composite copper foil is developed with a layer of acicular copper oxide, a nickel layer, and a silane coupling agent layer, where the silane coupling agent is applied at a specific amount to enhance both mechanical and chemical adhesion to resin base materials, while maintaining optimal surface roughness and area ratios.
The composite copper foil achieves excellent adhesion and reduces transmission loss, outperforming conventional methods by ensuring uniform plating and appropriate silane coupling agent application, resulting in improved high-frequency characteristics and etching properties.
Smart Images

Figure 0007601400000014 
Figure 0007601400000001 
Figure 0007601400000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite copper part treated with a silane coupling agent. [Background technology]
[0002] Copper foil used in printed wiring boards is required to have good adhesion to resin substrates. In order to improve this adhesion, a method has been used in which the surface of the copper foil is roughened by etching or the like to increase the mechanical adhesive strength by the so-called anchor effect. On the other hand, from the viewpoint of increasing the density of printed wiring boards and transmission loss in high frequency bands, flattening of the copper foil surface has become necessary. In order to meet these conflicting requirements, a copper surface treatment method has been developed that performs an oxidation step and a reduction step (WO 2014 / 126193). In this method, the copper foil is preconditioned, and then immersed in a chemical solution containing an oxidizing agent to oxidize the copper foil surface and form copper oxide irregularities, and then immersed in a chemical solution containing a reducing agent to reduce the copper oxide, thereby adjusting the surface irregularities and smoothing the surface roughness. Other methods that have been developed to improve adhesion in copper foil treatment using oxidation / reduction include a method of adding surface active molecules in the oxidation process (JP Patent Publication No. 2013-534054) and a method of forming a protective film on the surface of copper foil using an aminothiazole-based compound or the like after the reduction process (JP Patent Publication No. 8-97559).
[0003] Furthermore, in order to increase the adhesion between the copper foil and the insulating resin substrate, a silane coupling agent treatment was also used to increase the chemical adhesive strength. Silane coupling agents have the following chemical structure: X-Si(OR)3 (X: A reactive organic functional group such as a vinyl group, an epoxy group, an amino group, a methacryl group, or a mercapto group, which chemically bonds with the organic resin in the resin substrate; -OR is an alkoxy group such as a methoxy group, ethoxy group, dialkoxy group, or trialkoxy group, which hydrolyzes to generate a silanol group (SiOH) and bond with inorganic materials such as copper foil. It is expressed as:
[0004] In the case of a copper foil that has been roughened, it is known that the optimum amount of silane coupling agent varies depending on the method of roughening. In Patent Document 4, the silane coupling agent is 0.15 to 20.0 mg / m 2 (Si equivalent), and preferably 0.15 mg / m 2 However, in Patent Document 5, the silane coupling agent is used in an amount of 0.03 to 3.00 mg / m2, and it is described that the adhesion between the base resin and the surface-treated copper foil cannot be improved when the amount is less than 0.03 to 3.00 mg / m2. 2 It is described that it is preferable that the silane coupling agent adheres to the roughened surface in an amount of 0.05 mg / m2 (calculated as Si), and Patent Document 6 describes that the amount of the silane coupling agent present on the roughened surface is 0.05 mg / m2 (calculated as Si). 2 More than 1.5mg / m 2 It is stated that it is preferable that the .gamma. The optimum amount of the silane coupling agent depends not only on the roughness of the surface to which it is applied, but also on the type of metal laminated on the copper foil surface. For example, WO 2006 / 134868 describes that the adhesion efficiency of the tin plating layer and the silane coupling agent layer is excellent, and the silane coupling agent is applied on the tin plating layer, whereas JP 6248231 describes that the silane coupling agent is applied to a surface (i.e., pure copper) that has been roughened by electrolytic deposition of copper particles, or a surface that has been electrolytically plated with nickel, zinc, chromium, etc., on the surface, and WO 2017 / 099094 describes that the surface that has been roughened by electrolytic deposition of molybdenum particles is nickel-plated and then treated with the silane coupling agent.
[0005] The inventors of the present application had also developed a composite copper foil in which an oxidation-treated copper foil was plated with nickel by electrolytic plating. However, the surface roughness and composition of the composite copper foil were different from those of conventional copper foils, and the optimal amount of silane coupling agent to be applied was unknown (WO 2019 / 093494). Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention provides a composite copper foil treated with a silane coupling agent. [Means for solving the problem]
[0007] As a result of extensive research, the inventors of the present application have succeeded in producing a composite copper component that has excellent mechanical and chemical adhesion to a resin substrate by precipitating needle-like copper oxide through an oxidation treatment, forming a nickel layer on the roughened surface of the copper component by electrolytic plating, and coating the surface with the nickel layer with a silane coupling agent.
[0008] The present invention includes the following aspects: [1] A composite copper member having a layer containing needle-shaped copper oxide on at least a part of the surface of a copper member, a nickel layer on the layer containing copper oxide, and a silane coupling agent layer on the surface on which the nickel layer is formed, wherein the adhesion amount of the silane coupling agent layer is 7 μg / dm 2 More than 900μg / dm 2 A composite copper component having the following (Si converted weight per unit area of copper component): [2] The composite copper member according to [1], wherein the BET surface area ratio of the surface on which the silane coupling agent layer is formed (surface area of the surface on which the silane coupling agent layer is formed / planar field area of the copper member on which the silane coupling agent layer is formed, calculated by the BET method) is 3 or more and 20 or less. [3] The thickness of the nickel layer is 0.5 mg / dm 2 More than 25mg / dm 2 The composite copper member according to [1] or [2], wherein the nickel weight per unit area of the copper member is the following: [4] The composite copper member according to any one of [1] to [3], wherein the surface on which the silane coupling agent layer is formed has an Ra of 0.02 μm or more and 0.17 μm or less. [5] The composite copper member according to any one of [1] to [4], wherein the surface on which the silane coupling agent layer is formed has an Rz of 0.2 μm or more and 1.5 μm or less. [6] The BET surface area ratio / Rz value of the surface on which the silane coupling agent layer is formed is 4 μm -1 The composite copper member according to any one of [1] to [5] above. [7] The silane coupling agent is represented by the following formula: Y—Si(OR)3 (Y is selected from the group consisting of vinyl, epoxy, amino, methacryl, mercapto, 3-mercaptopropyl, 3-aminopropyl, 3-mercaptopropyl, 2-(3,4-epoxycyclohexyl)ethyl, 3-methacryloxypropyl, 3-isocyanatopropyl, 3-ureidopropyl and 3-acryloxypropyl groups; The composite copper member according to any one of [1] to [6], comprising a compound represented by the following formula:--OR is an alkoxy group. [8] A laminate obtained by laminating a resin base material on the silane coupling agent layer of the composite copper member according to any one of [1] to [7]. [9] A printed wiring board comprising the laminate according to [8].
[10] The composite copper member according to any one of [1] to [7], wherein the copper member is a copper foil.
[11] A negative electrode current collector comprising the composite copper member according to
[10] .
[0009]
[12] A method for producing a composite copper component treated with a silane coupling agent, comprising: a first step of forming a copper oxide layer having an average thickness of 400 nm or less and a fine uneven shape on at least a part of a surface of a copper member by oxidation treatment; a second step of forming a nickel layer on the copper oxide layer by electrolytic plating; The surface on which the nickel layer is formed is coated with 7 μg / dm 2 More than 900μg / dm 2 A third step of coating the copper member with a silane coupling agent of the following amount (weight in terms of Si per unit area of the copper member): Manufacturing method.
[13] The manufacturing method according to
[12] , wherein the surface on which the copper oxide layer is formed after the first step has an Ra of 0.035 or more and 0.15 or less.
[14] The method according to
[12] or
[13] , wherein the surface on which the copper oxide layer is formed after the first step has an Rz of 0.25 or more and 1.45 or less.
[15] The current density of the electrolytic plating process in the second step is 5A / dm 2 The method for producing the same according to any one of
[12] to
[14] , characterized in that:
[16] The thickness of the nickel layer is 0.5 mg / dm 2 More than 25mg / dm 2 The method according to any one of
[12] to
[15] , wherein the nickel weight per unit area of the copper member is below 100%.
[17] The silane coupling agent is represented by the following formula: X—Si(OR)3 (X is selected from the group consisting of vinyl, epoxy, amino, methacryl, mercapto, 3-mercaptopropyl, 3-aminopropyl, 3-mercaptopropyl, 2-(3,4-epoxycyclohexyl)ethyl, vinyl, 3-methacryloxypropyl, 3-isocyanatopropyl, 3-ureidopropyl and 3-acryloxypropyl groups; The method according to any one of
[12] to
[16] , comprising a compound represented by the formula (I)--OR is an alkoxy group.
[18] The method according to any one of
[12] to
[17] , wherein the surface coated with the silane coupling agent after the third step has an Ra of 0.02 μm or more and 0.17 μm or less.
[19] The method according to any one of
[12] to
[18] , wherein the Rz of the surface coated with the silane coupling agent after the third step is 0.2 μm or more and 1.5 μm or less.
[20] The method according to any one of
[12] to
[19] , wherein the BET surface area ratio of the surface coated with the silane coupling agent after the third step is 3 or more and 20 or less.
[21] After the third step, the BET surface area ratio / Rz value of the surface coated with the silane coupling agent is 4μm -1 The method for producing a product according to any one of
[12] to
[20] above.
[22] A method for producing a laminate, comprising a step of thermocompression bonding a resin substrate to a copper member treated with a silane coupling agent produced by the method for producing a laminate according to any one of
[12] to
[21] .
[23] The method according to any one of
[12] to
[21] , wherein the copper member is a copper foil.
[24] A method for manufacturing a secondary battery, comprising a step of coating and supporting a conductive active material on a composite copper member treated with a silane coupling agent produced by the manufacturing method described in
[23] . ==Cross references to related literature== This application claims priority based on Japanese Patent Application No. 2019-236800, filed on December 26, 2019, and the basic application is incorporated herein by reference. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 shows cross-sectional images (magnification: 50,000 times) of Example 1 and Comparative Example 10 observed with a scanning electron microscope (SEM). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings, but are not necessarily limited thereto. The objects, features, advantages, and ideas of the present invention will be apparent to those skilled in the art from the description in this specification, and those skilled in the art can easily reproduce the present invention from the description in this specification. The embodiments and specific examples of the invention described below show preferred embodiments of the present invention, and are shown for illustrative or explanatory purposes, and do not limit the present invention thereto. It is apparent to those skilled in the art that various modifications and alterations can be made based on the description in this specification within the intent and scope of the present invention disclosed in this specification.
[0012] ==Manufacturing method of composite copper parts treated with silane coupling agent== One embodiment of the present invention is a method for producing a composite copper member treated with a silane coupling agent, the method comprising a first step of precipitating needle-like copper oxide on a copper foil surface by oxidation treatment to form a copper oxide layer having a fine uneven shape, a second step of forming a nickel layer on the copper oxide layer by electrolytic plating treatment, and a third step of coating the surface on which the nickel layer has been formed with a silane coupling agent. The copper member is a material that contains Cu as a main component and is a part of the structure, and includes, but is not limited to, copper foil such as electrolytic copper foil, rolled copper foil, and copper foil with a carrier, copper wire, copper plate, copper lead frame, copper powder, etc. Those that can be electroplated are preferable. The copper foil includes copper foils containing copper as a main component, such as electrolytic copper foils, rolled copper foils, and copper foils with carriers, and has a thickness of 0.1 μm to 100 μm, and more preferably 0.5 μm to 50 μm. The copper plate refers to a plate-shaped material whose main component is copper and whose thickness exceeds 100 μm. Although not particularly limited, the thickness is preferably 1 mm or more, 2 mm or more, or 10 mm or more, and is preferably 10 cm or less, 5 cm or less, or 2.5 cm or less. The copper member is preferably a copper foil made of pure copper having a Cu purity of 95% by mass or more, 99% by mass or more, or 99.9% by mass or more, more preferably made of tough pitch copper, deoxidized copper, or oxygen-free copper, and even more preferably made of oxygen-free copper having an oxygen content of 0.001% by mass to 0.0005% by mass.
[0013] In the first step, the copper foil is oxidized to precipitate needle-shaped copper oxide, forming a copper oxide layer having a fine uneven shape. The method of formation is not particularly limited, but it may be formed using an oxidizing agent, or may be formed by heat treatment or anodic oxidation. A roughening treatment step such as etching is not necessary before this oxidation step, but may be performed. An alkali treatment may be performed to prevent the introduction of acid into the degreasing and cleaning or oxidation step. The method of the alkali treatment is not particularly limited, but it is sufficient to treat the copper foil with an alkali aqueous solution of preferably 0.1 to 10 g / L, more preferably 1 to 2 g / L, such as a sodium hydroxide aqueous solution, at 30 to 50° C. for about 0.5 to 2 minutes.
[0014] The oxidizing agent is not particularly limited, and for example, an alkaline aqueous solution containing hypochlorite (e.g., sodium salt or potassium salt), chlorite, chlorate, perchlorate, etc. Various additives (e.g., phosphates such as trisodium phosphate dodecahydrate) and surface active molecules may be added to the oxidizing agent to adjust the precipitation of copper oxide. Surface active molecules include porphyrins, porphyrin macrocycles, expanded porphyrins, ring-contracted porphyrins, linear porphyrin polymers, porphyrin sandwich coordination complexes, porphyrin arrays, silanes, tetraorgano-silanes, aminoethyl-aminopropyl-trimethoxysilane, 3-aminopropyl)trimethoxysilane, 1-[3-(trimethoxysilyl)propyl]urea, (3-aminopropyl)triethoxysilane, (3-glycidyloxypropyl)trimethoxysilane, (3-chloropropyl)trimethoxysilane, and 1-[3-(trimethoxysilyl)propyl]urea. Examples include silane, (3-glycidyloxypropyl)trimethoxysilane, dimethyldichlorosilane, 3-(trimethoxysilyl)propyl methacrylate, ethyltriacetoxysilane, triethoxy(isobutyl)silane, triethoxy(octyl)silane, tris(2-methoxyethoxy)(vinyl)silane, chlorotrimethylsilane, methyltrichlorosilane, silicon tetrachloride, tetraethoxysilane, phenyltrimethoxysilane, chlorotriethoxysilane, ethylenetrimethoxysilane, amines, and sugars. As an example of the oxidation treatment liquid, an aqueous solution containing sodium chlorite at 30 g / L or more and 250 g / L or less, potassium hydroxide at 8 g / L or more and 40 g / L or less, and 3-glycidyloxypropyltrimethoxysilane at 0.5 g / L or more and 2 g / L or less can be used.
[0015] The oxidation reaction conditions are not particularly limited, but the liquid temperature of the oxidizing agent is preferably 40 to 95° C., and more preferably 45 to 80° C. The reaction time is preferably 0.5 to 30 minutes, and more preferably 1 to 10 minutes.
[0016] In the first step, the oxide layer formed by the oxidation treatment may be dissolved with a solvent to adjust the irregularities on the surface of the oxide layer.
[0017] The dissolving agent used in this step is not particularly limited, but is preferably a chelating agent, in particular a biodegradable chelating agent, and examples thereof include ethylenediaminetetraacetic acid, diethanolglycine, tetrasodium L-glutamic acid diacetate, ethylenediamine-N,N'-disuccinic acid, sodium 3-hydroxy-2,2'-iminodisuccinate, trisodium methylglycine diacetate, tetrasodium aspartic acid diacetate, disodium N-(2-hydroxyethyl)iminodiacetate, and sodium gluconate.
[0018] The pH of the dissolving agent is not particularly limited, but is preferably alkaline, more preferably pH 8 to 10.5, even more preferably pH 9.0 to 10.5, and even more preferably pH 9.8 to 10.2.
[0019] In the first step, the copper oxide layer formed on the copper member may be reduced using a chemical solution containing a reducing agent (chemical solution for reduction) to adjust the number and height of the protrusions.
[0020] The reducing agent may be DMAB (dimethylamine borane), diborane, sodium borohydride, hydrazine, etc. The reducing chemical is a liquid containing a reducing agent, an alkaline compound (sodium hydroxide, potassium hydroxide, etc.), and a solvent (pure water, etc.).
[0021] In the first step, the thickness of the copper oxide layer is set to 400 nm or less on average. Preferably, the thickness is set to 200 nm or less on average, more preferably, 160 nm or less on average, or 90 nm or less on average. Furthermore, the thickness of the copper oxide layer is preferably set to 20 nm or more on average, more preferably, 30 nm or more on average, and even more preferably, 40 nm or more on average. The ratio of the area in the copper oxide layer having a thickness of 400 nm or less is not particularly limited, but it is preferable that 50% or more is 400 nm or less, more preferably, 70% or more is 400 nm or less, even more preferably, 90% or more is 400 nm or less, even more preferably, 95% or more is 400 nm or less, and even more preferably, almost 100% is 400 nm or less. The thickness ratio of the copper oxide layer can be calculated, for example, by a continuous electrochemical reduction method (SERA) at 10 measurement points in an area of 10×10 cm.
[0022] The arithmetic mean roughness (Ra) of the copper oxide layer is preferably 0.035 μm or more, more preferably 0.038 μm or more, and is preferably 0.20 μm or less, more preferably 0.060 μm or less. The maximum height roughness (Rz) of the copper oxide layer is preferably 0.2 μm or more, more preferably 0.25 μm or more, and is preferably 1.45 μm or less, more preferably 0.50 μm or less. The arithmetic mean roughness (Ra) is the average of the absolute values of Z(x) (i.e. the height of the peaks and the depth of the valleys) in the profile curve (y=Z(x)) expressed by the following formula over a reference length l.
number
[0023] In the second step, the copper oxide layer formed in the first step is subjected to electrolytic plating to form a nickel layer. The nickel layer is formed by electrolytic plating. The nickel content in the nickel layer is preferably 90% by weight or more, 95% by weight or more, 98% by weight or more, 99% by weight or more, or 99.9% by weight or more. The average thickness of the nickel layer formed by electrolytic plating is 0.5 mg / dm2 when expressed as the weight of nickel per unit area of the copper foil on which the nickel layer is formed (planar area of the copper foil in the case of single-sided plating, and planar area of the copper foil x 2 in the case of double-sided plating). 2 , 1.0 mg / dm 2 , 1.5 mg / dm 2 , 2.0 mg / dm 2 , 3.0 mg / dm 2 , 4.0 mg / dm 2 , 5.0 mg / dm 2 , 6.0 mg / dm 2 , or 7.0 mg / dm 2 More preferably, it is 25.0 mg / dm or more. 2 , 20.0 mg / dm 2 , 15.0 mg / dm 2 , 10.0 mg / dm 2 , 9.0 mg / dm 2 , or 9.0 mg / dm 2 It is preferable that the following is true: The planar area of a copper foil is equal to the surface area of a given area if the surface of that area were flat, and corresponds to the defined area in the "developed area ratio (sdr) (ISO25178)". The average thickness of the nickel layer can be calculated by dissolving the nickel forming the nickel layer in an acidic solution, measuring the amount of nickel by ICP analysis, and dividing the measured amount by the unit area of the copper foil on which the nickel layer is formed. Alternatively, it can be calculated by dissolving the copper foil having the nickel layer itself and detecting and measuring only the amount of nickel forming the nickel layer.
[0024] In electrolytic plating, an electric charge is required to partially reduce the oxide in the oxide layer. Therefore, when nickel is applied to copper foil, in order to keep the thickness within the preferred range, a charge of 15 C / dm2 is required per area of copper foil to be electrolytically plated. 2 Above ~90C / dm 2 It is preferred to provide the following charges: The current density is 5A / dm 2 The following is preferable. If the current density is too high, plating will concentrate on the convex parts, making uniform plating difficult. The current may be different until the oxide in the copper oxide layer is partially reduced and during plating. Also, the current is appropriately adjusted to obtain a predetermined thickness depending on the metal to be coated. As a supplying agent for plating ions, for example, nickel sulfate, nickel sulfamate, nickel chloride, nickel bromide, etc. can be used. Other additives including pH buffers and gloss agents include, for example, boric acid, nickel acetate, citric acid, sodium citrate, ammonium citrate, potassium formate, malic acid, sodium malate, sodium hydroxide, potassium hydroxide, sodium carbonate, ammonium chloride, sodium cyanide, potassium sodium tartrate, potassium thiocyanate, sulfuric acid, hydrochloric acid, potassium chloride, ammonium sulfate, ammonium chloride, potassium sulfate, sodium sulfate, sodium thiocyanate, sodium thiosulfate, potassium bromate, potassium pyrophosphate, ethylenediamine, nickel ammonium sulfate, sodium thiosulfate, hydrofluoric acid, sodium silicofluoride, strontium sulfate, cresol sulfonic acid, β-naphthol, saccharin, 1,3,6-naphthalene trisulfonic acid, naphthalene (di, tri), sodium sulfonate, sulfonamide, and sulfinic acid. In nickel plating, the bath composition preferably contains, for example, nickel sulfate (100 g / L or more and 350 g / L or less), nickel sulfamate (100 g / L or more and 600 g / L or less), nickel chloride (0 g / L or more and 300 g / L or less), or a mixture thereof, but may also contain additives such as sodium citrate (0 g / L or more and 100 g / L or less) or boric acid (0 g / L or more and 60 g / L or less).
[0025] In the third step, the surface after the electrolytic plating is treated with a silane coupling agent. The silane coupling agent used is preferably one having 2 or 3 hydrolyzable groups, and the hydrolyzable group is preferably a methoxy group or an ethoxy group. Although there are no particular limitations, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, vinyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-ureidopropyltrialkoxysilane, 3-acryloxypropyltrimethoxysilane, and the like can be used. The silane coupling agent treatment can be carried out by applying or spraying a solution in which the silane coupling agent is dispersed in water or an organic solvent, and allowing it to be adsorbed. The solution in which the silane coupling agent is dispersed in water or an organic solvent is not particularly limited, but is preferably 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, or 9% or more by weight, and preferably 20%, 15%, or 10% or less by weight. After adsorption, the silane coupling agent treatment is completed by drying. The temperature and time for drying are not particularly limited as long as the water or organic solvent as the solvent is completely evaporated, but drying at 70°C for 1 minute or more is preferable, drying at 100°C for 1 minute or more is more preferable, and drying at 110°C for 1 minute or more is even more preferable.
[0026] The arithmetic mean roughness (Ra) of the surface on which the coupling agent layer is formed after the coupling agent treatment is preferably 0.01 μm, 0.02 μm, 0.03 μm or 0.04 μm or more, and more preferably 0.20 μm, 0.15 μm, 0.10 μm or 0.060 μm or less. The maximum height roughness (Rz) of the surface on which the coupling agent layer is formed after the coupling agent treatment is preferably 0.2 μm, 0.3 μm or 0.4 μm or more, and is preferably 1.5 μm, 1.4 μm, 1.3 μm, 1.2 μm, 1.1 μm, 1.0 μm, 0.50 μm, 0.40 μm or 0.30 μm or less. In addition, the change in surface roughness, which is expressed as the ratio of Ra after oxidation treatment to Ra after coupling agent treatment (Ra after oxidation treatment / Ra after coupling agent treatment), is preferably 0.7 to 1.3, and the ratio of Rz after oxidation treatment to Rz after coupling agent treatment (Rz after oxidation treatment / Rz after coupling agent treatment) is preferably 0.8 to 1.2. Since the coupling agent layer is extremely thin, the closer this ratio is to 1, the more uniform and even the thickness of the nickel layer formed by electrolytic plating is.
[0027] By carrying out the first to third steps, a composite copper foil can be produced which has a layer containing acicular copper oxide on at least a portion of the surface of the copper foil, a nickel layer laminated on the layer containing copper oxide, and further has a silane coupling agent layer on the surface on which the nickel layer is laminated.
[0028] ==Composite copper member with silane coupling agent layer== One embodiment of the present invention is a composite copper member having a layer containing needle-shaped copper oxide on at least a portion of the surface of a copper member, a nickel layer laminated on the layer containing copper oxide, and a silane coupling agent layer on the surface on which the nickel layer is laminated.
[0029] The amount of the silane coupling agent layer is 5 μg / dm2 when expressed as the weight of Si atoms per unit area of the copper foil (planar area of the copper foil in the case of single-sided treatment, and planar area of the copper foil x 2 in the case of double-sided treatment) on the surface on which the silane coupling agent layer is formed. 2 , 6μg / dm2 , 7μg / dm 2 , 8μg / dm 2 , 9μg / dm 2 , 10μg / dm 2 , 15μg / dm 2 , 20μg / dm 2 , 30μg / dm 2 , 40μg / dm 2 , 50μg / dm 2 or 60 μg / dm 2 It is preferable that the concentration is 900 μg / dm or more. 2 , 700μg / dm 2 , 500μg / dm 2 , 400μg / dm 2 , 300μg / dm 2 , 200g / dm 2 , 100μg / dm 2 , 70μg / dm 2 , 60μg / dm 2 , or 50 μg / dm 2 It is preferable that the following is true: The amount of the silane coupling agent layer can be calculated by dissolving the nickel layer with the silane coupling agent layer formed on its surface in an acidic solution, measuring the amount of Si atoms by ICP analysis, and dividing the measured amount by the unit area of the copper foil. Alternatively, the composite copper foil with the silane coupling agent layer itself can be dissolved, and only the amount of Si atoms forming the silane coupling agent layer can be detected and measured to calculate the amount of the silane coupling agent layer.
[0030] The surface area is preferably calculated by the BET method, but is not limited thereto. For example, the surface area can be calculated by image processing such as 3D image analysis. Two-dimensional observation images of the copper foil are continuously observed, and the observation images are reconstructed in 3D. For the observation, a scanning electron microscope (SEM), a transmission electron microscope (TEM), a confocal microscope, etc. may be used. When using an SEM, processing is performed using a FIB (focused ion beam), and cross-sectional observation of the entire processed copper foil is performed, and the observation images are accumulated. When using a TEM, an electron beam is irradiated onto the continuously tilted copper foil, and successive tilt images (2D projection images of mass density distribution) at each angle are captured. After alignment of the successive tilt images, a 3D image is constructed by Fourier transform and inverse Fourier transform.
[0031] BET specific surface area refers to the total surface area per mass of solid particles calculated by the gas adsorption method (BET method), in which gas molecules such as nitrogen (N2), argon (Ar), krypton (Kr), and carbon monoxide (CO) are adsorbed onto solid particles and the specific surface area of the solid particles is measured from the amount of adsorbed gas molecules. Methods for measuring the BET specific surface area include the krypton gas adsorption BET multipoint method and the nitrogen adsorption single point method. When measuring a particularly fine surface area, krypton gas is preferred due to its saturated vapor pressure. The total surface area of the composite copper foil can be calculated by (BET specific surface area)×(mass of copper foil used).
[0032] The BET surface area ratio can be expressed as (the surface area of the surface on which the silane coupling agent layer is formed, calculated by the BET method) / (the planar view area of the copper foil on which the silane coupling agent layer is formed). In the copper foil used in the present invention, the surface area of the copper foil side portion can be ignored, so the BET surface area ratio is (1) In the case of copper foil treated on both sides TIFF0007601400000002.tif22170 (2) In the case of copper foil treated on one side TIFF0007601400000003.tif23170 It can be calculated as follows.
[0033] When the thickness is 100 μm or more, such as in the case of a copper plate, the surface area of the side portion cannot be ignored. When the thickness is 100 μm or more, the BET surface area ratio is (1) In the case of copper plates treated on both sides TIFF0007601400000004.tif22170 (2) In the case of copper sheets treated on one side This can be calculated using TIFF0007601400000005.tif22170. The BET surface area ratio of the surface on which the silane coupling agent layer is formed is preferably 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, or 10 or more, and is preferably 20 or less, 15 or less, 14 or less, 13 or less, 12 or less, or 11 or less.
[0034] The BET surface area ratio / Rz value of the surface on which the silane coupling agent layer is formed is 4μm -1 More than 5μm -1 More than 10μm -1 Above, 15μm -1 More than or equal to 20μm -1 More than 35μm is preferable. -1 Below, 30μm -1 Less than or equal to 25μm -1 The following is preferred:
[0035] ==Method of using a composite copper member having a silane coupling agent layer== The composite copper member treated with the silane coupling agent according to the present invention can be used as copper foil for printed wiring boards, copper foil for LIB negative electrode current collectors, and the like. For example, a laminate can be prepared by bonding the composite copper foil treated with the silane coupling agent according to the present invention to a resin substrate in a layered manner, and the laminate can be used to manufacture a printed wiring board. The type of resin contained in the resin substrate is not particularly limited, but may be a thermoplastic resin or a thermosetting resin, and is preferably polyphenylene ether (PPE), epoxy, polyphenylene oxide (PPO), polybenzoxazole (PBO), polytetrafluoroethylene (PTFE), liquid crystal polymer (LCP), triphenylphossite (TPPI), fluororesin, polyetherimide, polyetheretherketone, polycycloolefin, bismaleimide resin, low dielectric constant polyimide, cyanate resin, or a mixture of these resins. The resin substrate may further contain an inorganic filler or glass fiber. In addition, for example, when a negative electrode current collector is produced using a composite copper foil treated with the silane coupling agent according to the present invention, the adhesion between the copper foil and the negative electrode material is improved, and a good lithium ion battery with little capacity deterioration can be obtained. The negative electrode current collector for lithium ion batteries can be produced according to a known method. For example, a negative electrode material containing a carbon-based active material is prepared and dispersed in a solvent or water to form an active material slurry. This active material slurry is applied to a composite copper foil treated with the silane coupling agent according to the present invention, and then dried to evaporate the solvent and water. Thereafter, the composite copper foil is pressed and dried again, and then the negative electrode current collector is formed into a desired shape. The negative electrode material may contain silicon or a silicon compound, germanium, tin, lead, etc., which have a larger theoretical capacity than the carbon-based active material. In addition, not only an organic electrolyte solution in which a lithium salt is dissolved in an organic solvent as an electrolyte, but also a polymer made of polyethylene oxide or polyvinylidene fluoride may be used. The composite copper foil treated with the silane coupling agent according to the present invention can be applied not only to lithium ion batteries but also to lithium ion polymer batteries. EXAMPLES
[0036] <1. Manufacturing of composite copper foil> In Examples 1 to 27 and Comparative Examples 1 to 9, DR-WS (manufactured by Furukawa Electric Co., Ltd., thickness: 18 μm) was used as the copper foil. In Comparative Example 10, FV-WS (manufactured by Furukawa Electric Co., Ltd., thickness: 18 μm) that had already been roughened and plated on only one side was used. In Example 16, only the shiny side (the shiny side, which is flat compared to the opposite side) of the DR-WS was subjected to oxidation treatment and electrolytic plating treatment.
[0037] (1) Pretreatment [Alkaline degreasing treatment] The copper foil was immersed in a 40 g / L aqueous solution of sodium hydroxide at a liquid temperature of 50° C. for 1 minute, and then rinsed with water. [Acid cleaning treatment] The copper foil that had been subjected to the alkaline degreasing treatment was immersed in a 10% by weight aqueous sulfuric acid solution at a liquid temperature of 25° C. for 2 minutes, and then rinsed with water. [Pre-dip processing] The copper foil that had been subjected to the acid cleaning treatment was immersed for 1 minute in a pre-dip chemical solution containing 1.2 g / L of sodium hydroxide (NaOH) at a liquid temperature of 40°C.
[0038] (2) Oxidation treatment In Examples 1 to 15, 17 to 27 and Comparative Examples 1 to 7 and 9, the copper foils that had been subjected to the alkali treatment were immersed in the aqueous oxidation treatment solution shown in Table 1 under the prescribed conditions to perform the oxidation treatment on both sides. In Example 16, the copper foil was floated on the surface of the aqueous oxidation treatment solution shown in Table 1 to perform the oxidation treatment on only one side. After these treatments, the copper foil was washed with water.
[0039] (3) Plating In Examples 1 to 15, 17 to 27 and Comparative Examples 1 to 9, nickel plating was performed on both sides using a nickel plating electrolyte (nickel sulfate 230 g / L; boric acid 25 g / L) under the conditions shown in Table 1. In Example 16, plating was performed on only one side under the conditions shown in Table 1 by placing an anode electrode only on the side to be plated.
[0040] (4) Coupling treatment In Examples 1 to 4, 6 to 27 and Comparative Examples 3 to 9, the silane coupling agent solution shown in Table 1 was applied to one side, and after removing excess silane coupling agent with a bar coater, the substrate was treated at 70° C. for 1 minute. In Example 5 and Comparative Examples 1 and 2, the substrate was immersed in the silane coupling agent solution shown in Table 1, and then treated on both sides at 110° C. for 1 minute. Silane coupling agents (3-mercaptopropyltrimethoxysilane (KBE-903); 3-aminopropyltrimethoxysilane (KBM-903); 3-mercaptopropyltrimethoxysilane (KBM-803); 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (KBM-303); vinyltrimethoxysilane (KBM-1003); 3-methacryloxypropyltrimethoxysilane (KBM-502); 3-isocyanatopropyltriethoxysilane (KBE-9007N); 3-ureidopropyltrialkoxysilane (KBE-585); 3-acryloxypropyltrimethoxysilane (KBM-5103)) were purchased from Shin-Etsu Silicones.
[0041] A plurality of test pieces were prepared under the same conditions for each of the examples and comparative examples. Since the comparative example 10 was a commercially available product, it was used as the test piece without undergoing the treatments (1) to (4). Cross-sectional images (magnification 50,000 times) of Example 1 and Comparative Example 10 observed with a scanning electron microscope (SEM) are shown in Fig. 1. In Example 1, needle-like protrusions (arrows) of approximately the same thickness caused by acicular (crystal) copper oxide and plated with crystalline nickel were observed, whereas bump-like protrusions (arrows) of different sizes caused by electrodeposition of copper particles were observed in Comparative Example 10. Such needle-like protrusions cannot be observed if the nickel plating layer is too thick (for example, Comparative Example 5).
[0042] [Table 1] TIFF0007601400000007.tif171160TIFF0007601400000008.tif126160
[0043] <2. Calculation of the amount of nickel and silane coupling agent attached> The amount of nickel and silane coupling agent attached was determined by dissolving copper foil in 12% nitric acid, measuring the Ni and Si concentrations in the resulting solution using an ICP optical emission spectrometer 5100 SVDV ICP-OES (Agilent Technologies), and calculating the amount of Ni and Si per unit area of the copper foil used (planar area of the copper foil in the case of single-sided treatment, planar area of the copper foil x 2 in the case of double-sided treatment).
[0044] <3. Measurement of BET specific surface area> The BET specific surface area (actual total surface area per 1 g of copper foil) of each test piece was measured by the krypton gas adsorption BET multipoint method using a multi-sample high-performance specific surface area measurement device 3FLEX manufactured by Micromeritics Corp. Before the measurement, the specimens were pretreated by drying under reduced pressure at 100°C for 2 hours. The test pieces used for the measurement were cut into 110 pieces of 30 mm x 7 mm per 3.83 g of original copper foil and introduced into the measurement device. The results are shown in Table 2.
[0045] <4. Calculation of BET surface area ratio> The planar area per gram of the original copper foil used and the BET specific surface area measured above were used to calculate according to the following formula. (1) In the case of copper foils treated on both sides up to the second step (Examples 1 to 15, 17 to 27 and Comparative Examples 1 to 9) TIFF0007601400000009.tif22170(2) Copper foil treated on one side up to the second step (Example 16) and Comparative Example 10 TIFF0007601400000010.tif23170The results are shown in Table 2.
[0046] <5. Calculation of Ra and Rz> The surface shape of the copper foil treated with the coupling agent (when both sides were treated, the surface with the smaller roughness of the original foil) was measured using a confocal scanning electron microscope OPTELICS H1200 (manufactured by Lasertec Corporation), and Ra and Rz were calculated according to the method specified in JIS B 0601:2001 (based on the international standard ISO4287-1997). The measurement conditions were a scan width of 100 μm, a scan type of area, a light source of Blue, and a cutoff value of 1 / 5. The object lens was set to x100, the contact lens to x14, the digital zoom to x1, and the Z pitch to 10 nm, and data was obtained from three locations, with Ra and Rz being the average values of the three locations. The results are shown in Table 2.
[0047] <6. Peel strength measurement> Each resin substrate was thermocompression bonded to the treated surface of each test piece (in the case of double-sided treatment, the surface of the original foil with the lesser roughness) under the following conditions. In the case of MEGTRON7 (Panasonic, thickness 100 μm), the material was heated to 110° C. using a vacuum press while pressing at 0.49 MPa, and then held at 210° C. and 2.94 MPa for 120 minutes for thermocompression bonding. In the case of Vecstar CT-Z film (LCP) (Kuraray, thickness 50 μm), it was heated at 0 MPa using a vacuum press until it reached 260°C, held for 15 minutes after reaching 260°C, and then pressed at 4 MPa while heating until it reached 300°C. It was then held at 300°C for 10 minutes for thermocompression. In the case of PIXEO FRS (PI) (manufactured by Kaneka Corporation, thickness 12.5 μm), thermocompression bonding was performed by holding the material at 350° C. and 5 MPa for 20 minutes using a vacuum press. The circuit board was prepared by masking with a 10 mm wide tape and etching.Then, the peel strength was measured when the copper foil was peeled from the resin at a speed of 50 mm / min in a 90° direction.
[0048] The evaluation criteria for peel strength are: When using MEGTRON7, ◎: 0.6kgf / cm or more ○: 0.5~0.6kgf / cm △: 0.4~0.5kgf / cm ×: Less than 0.4kgf / cm year; When using Bexstar CT-Z film (LCP), ◎: 0.5kgf / cm or more ○: 0.4~0.5kgf / cm △: 0.3~0.4kgf / cm ×: Less than 0.3kgf / cm year; When using PIXEO FRS(PI), ◎: 0.6kgf / cm or more ○: 0.5~0.6kgf / cm △: 0.4~0.5kgf / cm ×: Less than 0.4kgf / cm It was decided. The results are shown in Table 2. All of the examples showed good peel strength.
[0049] <8. Measurement of high frequency characteristics> Each test piece was thermocompression bonded to a 100μm thick MEGTRON7 to create a 200mm long microstrip line. The circuit width was 230μm and the characteristic impedance was 50Ω. A network analyzer was used to transmit high frequency signals up to 40GHz through this transmission line, and the transmission loss was measured. The evaluation standard for transmission loss is at 40 GHz. ◎:-9.5dB or more ○: Less than -9.5dB to -10dB or more ×: Less than -10dB It was decided. The results are shown in Table 2. All of the examples showed good results.
[0050] <8. Measurement of etching property> Each test piece was thermally bonded to MEGTRON7 to create a copper-clad laminate, which was then cut into a size of 10 cm x 10 cm and a copper foil pattern was formed by etching. 14The resistance on the resin substrate was measured using an ohm resistance meter, and the etching property was confirmed by whether it exceeded the maximum range (◎) or not (×). If metal residue remains on the surface of the resin substrate during etching, conductivity is obtained. If it exceeds the maximum range, conductivity is not obtained, indicating that the etching is good. The results are shown in Table 2. All of the examples showed good results.
[0051] In the third step, a silane coupling agent layer is formed. When the amount of silane coupling agent attached is small or absent as in Comparative Examples 1, 2, and 4, sufficient silane coupling agent is not attached to obtain adhesion, and adhesion cannot be ensured. When the amount of silane coupling agent attached is too excessive as in Comparative Example 3, adhesion cannot be ensured due to destruction of the silane coupling agent layer. In contrast, in the examples in which an appropriate amount of silane coupling agent was attached, good adhesion was shown to all resin substrates. In the second step, a nickel layer is formed. In Comparative Examples 5 and 6, excessive nickel was applied, and the fine uneven shape formed in the first step was buried, so that the anchor effect was not obtained and adhesion could not be ensured. The high frequency characteristics were also inferior to those of the Examples due to the influence of the magnetic permeability caused by the application of excessive nickel. In terms of etching properties, Comparative Example 6 was also not completely etched due to the application of excessive nickel, and nickel remained on the resin surface. In Comparative Example 9, the amount of nickel attached was insufficient, so the effect as a protective layer was not sufficiently obtained and adhesion could not be ensured. In contrast, the Examples in which an appropriate amount of nickel was attached showed good characteristics. In the first step, a copper oxide layer having a fine uneven shape is formed by oxidation treatment. In Comparative Example 7, an excessive uneven shape was formed in the first step, so that a sufficient protective layer could not be formed by nickel in the subsequent second step, and adhesion was not obtained. In addition, the roughness became too large, which adversely affected the high frequency characteristics and etching characteristics. In Comparative Example 8, the first step was not performed, so that a fine uneven shape was not formed, the anchor effect was low, and sufficient adhesion could not be ensured. In contrast, the examples having an appropriate fine uneven shape showed good characteristics.
[0052] As described above, the present invention is characterized by a large amount of silane coupling agent attached per unit area due to low roughness and large surface area. This makes it possible to obtain superior high frequency characteristics and adhesion compared to the copper foil having conventional roughening particles such as Comparative Example 10.
[0053] [Table 2] TIFF0007601400000012.tif152160TIFF0007601400000013.tif124160 [Industrial Applicability]
[0054] The present invention makes it possible to provide a novel composite copper member, a laminate and an electronic component using the same, a composite copper foil for high-frequency transmission, and a laminate for high-frequency transmission and an electronic component for high-frequency transmission using the same.
Claims
1. A composite copper member having a layer containing needle-shaped copper oxide on at least a part of the surface of a copper member, a nickel layer on the layer containing copper oxide, and a silane coupling agent layer on the surface on which the nickel layer is formed, wherein the amount of adhesion of the silane coupling agent layer is 7 μg / dm 2 900 μg / dm or more 2 The weight per unit area of the copper member is calculated as the weight converted into silicon. the Rz (calculated by the method defined in JIS B 0601:2001 (based on international standard ISO 4287-1997)) of the surface on which the silane coupling agent layer is formed is 0.2 μm or more and 1.5 μm or less; A composite copper member, wherein the nickel layer has a thickness of 0.5 mg / dm 2 or more and 10.0 mg / dm 2 or less (nickel weight per unit area of the copper member).
2. A composite copper member having a layer containing needle-shaped copper oxide on at least a portion of the surface of a copper member, a nickel layer on said copper oxide-containing layer, and a silane coupling agent layer on the surface on which said nickel layer is formed, wherein the adhesion amount of said silane coupling agent layer is 7 μg / dm2 or more and 900 μg / dm2 or less (Si converted weight per unit area of the copper member), the BET surface area ratio of the surface on which the silane coupling agent layer is formed (surface area of the surface on which the silane coupling agent layer is formed / planar view area of the copper member on which the silane coupling agent layer is formed, calculated by the BET method) is 3 or more and 20 or less; A composite copper member, wherein the nickel layer has a thickness of 0.5 mg / dm 2 or more and 10.0 mg / dm 2 or less (nickel weight per unit area of the copper member).
3. A composite copper member having a layer containing needle-shaped copper oxide on at least a portion of the surface of a copper member, a nickel layer on said copper oxide-containing layer, and further having a silane coupling agent layer on the surface on which the nickel layer is formed, wherein the adhesion amount of said silane coupling agent layer is 7 μg / dm2 or more and 900 μg / dm2 or less (Si converted weight per unit area of the copper member), A composite copper member having a peel strength of 0.4 kgf / cm or more when a resin substrate is thermocompression-bonded to a silane coupling agent layer of the composite copper member under specific conditions and then the composite copper member is peeled from the resin substrate in a 90° direction at a speed of 50 mm / min.
4. The BET surface area ratio of the surface on which the silane coupling agent layer is formed (surface area of the surface on which the silane coupling agent layer is formed / plan view area of the copper member on which the silane coupling agent layer is formed, calculated by the BET method) is 3 or more and 20 or less. The composite copper member according to claim 1 or 3.
5. The thickness of the nickel layer is 0.5 mg / dm 2 25mg / dm or more 2 5. The composite copper member according to claim 3 or 4, wherein the nickel weight per unit area of the copper member is equal to or less than 1.
6. The Ra (calculated by a method defined in JIS B 0601:2001 (in accordance with international standard ISO 4287-1997)) of the surface on which the silane coupling agent layer is formed is 0.02 μm or more and 0.17 μm or less. The composite copper member according to any one of claims 1 to 5.
7. The Rz (calculated by a method defined in JIS B 0601:2001 (based on international standard ISO 4287-1997)) of the surface on which the silane coupling agent layer is formed is 0.2 μm or more and 1.5 μm or less. The composite copper member according to any one of claims 2 to 6.
8. The BET surface area ratio / Rz (calculated by the method specified in JIS B 0601:2001 (based on international standard ISO 4287-1997)) of the surface on which the silane coupling agent layer is formed is 4 μm -1 The composite copper member according to any one of claims 1 to 7.
9. The silane coupling agent is represented by the following formula: Y―Si(OR) 3 (Y is selected from the group consisting of vinyl groups, epoxy groups, amino groups, methacryl groups, mercapto groups, 3-mercaptopropyl groups, 3-aminopropyl groups, 3-mercaptopropyl groups, 2-(3,4-epoxycyclohexyl)ethyl groups, 3-methacryloxypropyl groups, 3-isocyanatopropyl groups, 3-ureidopropyl groups, and 3-acryloxypropyl groups; The composite copper member according to any one of claims 1 to 8, comprising a compound represented by the formula (I) (wherein -OR is an alkoxy group).
10. A laminate in which a resin substrate is laminated on the silane coupling agent layer of a composite copper component described in any one of claims 1 to 9.
11. A printed wiring board comprising the laminate of claim 10.
12. The composite copper member according to any one of claims 1 to 9, wherein the copper member is a copper foil.
13. A negative electrode current collector comprising the composite copper member of claim 12.
14. A method for producing a composite copper component treated with a silane coupling agent, comprising: a first step of forming a needle-like copper oxide layer having an average thickness of 400 nm or less on at least a part of a surface of a copper member by oxidation treatment; a second step of forming a nickel layer having a thickness of 0.5 mg / dm 2 or more and 10.0 mg / dm 2 or less (nickel weight per unit area of the copper member) on the copper oxide layer by electrolytic plating; The surface on which the nickel layer is formed is coated with 7 μg / dm 2 900 μg / dm or more 2 A third step of coating the copper member with a silane coupling agent having an amount of the following (weight in terms of Si per unit area of the copper member): Manufacturing method.
15. A method for producing a composite copper component treated with a silane coupling agent, comprising the steps of: a first step of forming a needle-like copper oxide layer having an average thickness of 400 nm or less on at least a part of a surface of a copper member by oxidation treatment; a second step of forming a nickel layer on the copper oxide layer by electrolytic plating; a third step of coating the surface on which the nickel layer is formed with a silane coupling agent in an amount of 7 μg / dm 2 or more and 900 μg / dm 2 or less (weight in terms of Si per unit area of the copper member); A resin substrate is thermocompressed under specific conditions to a surface of the composite copper member treated with a silane coupling agent, and then the composite copper member is peeled from the resin substrate in a 90° direction at a speed of 50 mm / min. The peel strength is 0.4 kgf / cm or more. Manufacturing method.
16. The method according to claim 14 or 15, wherein the surface on which the copper oxide layer is formed after the first step has an Ra (calculated by a method specified in JIS B 0601:2001 (in accordance with international standard ISO 4287-1997)) of 0.035 or more and 0.15 or less.
17. The method according to any one of claims 14 to 16, wherein Rz (calculated by a method defined in JIS B 0601:2001 (based on international standard ISO 4287-1997)) of the surface on which the copper oxide layer is formed after the first step is 0.25 or more and 1.450 or less.
18. The current density of the electrolytic plating process in the second step is 5 A / dm 2 The method according to any one of claims 14 to 17, characterized in that:
19. The thickness of the nickel layer is 0.5 mg / dm 2 25mg / dm or more 2 The method according to any one of claims 15 to 18, wherein the nickel weight per unit area of the copper member is equal to or less than 100%.
20. The silane coupling agent is represented by the following formula: X―Si(OR) 3 (X is selected from the group consisting of vinyl groups, epoxy groups, amino groups, methacryl groups, mercapto groups, 3-mercaptopropyl groups, 3-aminopropyl groups, 3-mercaptopropyl groups, 2-(3,4-epoxycyclohexyl)ethyl groups, vinyl groups, 3-methacryloxypropyl groups, 3-isocyanatopropyl groups, 3-ureidopropyl groups, and 3-acryloxypropyl groups; The method according to any one of claims 14 to 19, comprising a compound represented by the formula (I) (-OR is an alkoxy group).
21. The Ra (calculated by the method defined in JIS B 0601:2001 (based on international standard ISO4287-1997)) of the surface coated with the silane coupling agent after the third step is 0.02 μm or more and 0.17 μm or less. The manufacturing method according to any one of claims 14 to 20.
22. The Rz (calculated by the method defined in JIS B 0601:2001 (based on international standard ISO4287-1997)) of the surface coated with the silane coupling agent after the third step is 0.2 μm or more and 1.5 μm or less. The manufacturing method according to any one of claims 14 to 21.
23. The method according to any one of claims 14 to 22, wherein the BET surface area ratio of the surface coated with the silane coupling agent after the third step is 3 or more and 20 or less.
24. The BET surface area ratio / Rz (calculated by the method specified in JIS B 0601:2001 (based on international standard ISO 4287-1997)) of the surface coated with the silane coupling agent after the third process is 4 μm -1 The method for producing the present invention according to any one of claims 14 to 23.
25. A method for manufacturing a laminate, comprising a step of thermocompression bonding a resin substrate to a copper member treated with a silane coupling agent produced by the manufacturing method described in any one of claims 14 to 24.
26. The method according to any one of claims 14 to 24, wherein the copper member is a copper foil.
27. A method for producing a secondary battery, comprising a step of coating and supporting a conductive active material on a composite copper member treated with a silane coupling agent produced by the method for producing a secondary battery according to claim 26.
Citation Information
Patent Citations
Copper clad laminated sheet, printed circuit board using the same and production of them
JP1996309918A
Surface-treated copper foil for printed circuit board, copper-clad laminate for printed circuit board, and printed circuit board
WO2017099094A1
